PENGARUH TECHNOLOGY ACCEPTANCE MODEL TERHADAP KEPUTUSAN MUZAKKI MEMBAYAR ZAKAT MELALUI FINTECH GOPAY (STUDI PADA MUZAKKI BAZNAS DKI JAKARTA) - Afiful Ichwan; Ruslan Abdul Ghofur (Ekonomi Islam, 2021)
Indonesia is one of the countries with the most Muslim population. but in Indonesia zakat so far the realization of its acceptance is far from the existing potential. Baznas as a government institution authorized to carry out the processing and distribution of Zakat funds continues to increase Zakat receipts by working together to bring innovative Zakat facilities through fintech Gopay, the results of this innovation with fintech Gopay have managed to help collect donations of 63 billion. By using the Technology Acceptance Model. the authors analyze and understand the factors in influencing the acceptance of use through technology. The formulation of the problem how the influence of the Technology Acceptance Model on the decision to pay Zakat through Fintech Gopay? The results of the study concluded that the Technology Acceptance Model (perceived usefulness and perceived ease of use) partially and simultaneously influences the decision to pay Zakat through Fintech Gopay Keywords: Technology Acceptance Model, Zakat, Gopay fintech, Decision.